Nutrition constraint to improved smallholder milk production in the Ethiopian highlands: The Selale experience - Varvikko, T. (Institute of Agricultural Research, 1993)
Metabolizable energy (ME) and crude protein (CP) of the stall-fed resources met half of the requirements of crossbred cows in the Central Ethiopian highlands. The average supply of ME and CP from stall-feeding supported a milk yield of 850 kg or 55 percent of the lactation yield. The additional ME and CP required was provided by grazing and/or from body reserves. Feeding of ME and CP was always slightly above maintenance and it never met the requirement for milk production. In addition to the constraints in the basal feed production and the availability of supplementary feeds on-farm, large herd sizes penalize the nutrition of individual animals. Increased feed production and feed budgeting according to actual requirements is necessary to utilize the genetic potential for milk production of crossbred dairy cows. Hay making soon after the long rains is a simple, practical way to improve the feeding on-farm.